An Efficient ECG Monitoring System using MQTT Protocol for Remote Patients in an IoT System - Pasha, Afroz; S. R., Nagaraja (International Journal of Intelligent Systems and Applications in Engineering, 2023)
The healthcare domain has undergone a significant transformation to the Internet of Things (IoT), which has enabled the real-time monitoring of vital signs in patients. Among these vital signs, Electrocardiogram (ECG) monitoring is pivotal in the diagnosis of cardiac abnormalities. In this research article, we introduce an IoT-based ECG detection system that leverages the Pan-Tompkins algorithm to ensure precise and dependable processing of ECG signals. This system allows for the remote monitoring of ECG signals, facilitating the early identification of cardiac irregularities and timely intervention. This paper encompasses the conception, implementation, and assessment of the proposed IoT-based ECG detection system, emphasizing its efficacy and potential impact on healthcare through the utilization of MQTT (Message Queuing Telemetry Transport). The paper illustrates how IoT technology can be applied in the healthcare domain, presenting a system designed for monitoring a patient's ECG remotely. This system consists of components such as the ESP8266, ECG Sensor, and Ubidots Cloud for real-time storage and visualization of ECG data, enabling the precise measurement of a remote patient's heart rate.